Across the sub-Arctics of Canada : a journey of 3,200 miles by canoe and snow shoe through the Hudson Bay region - Tyrrell, James Williams, 1863-1945.; Gordon, J. S., illustrator.; Heming, Arthur, 1871-1940, illustrator.; Gordon, J. S. illus.; Heming, Arthur, 1871-1940, illus. (Toronto : William Briggs, 1908)
Account of an expedition of geological exploration by the Tyrrell brothers in 1893, from Winnipeg to Edmonton, Fort Cipewyan, Chesterfield Inlet (Northwest Territories), Hudson's Bay and Churchill, Manitoba. Account of an expedition of geological exploration by the Tyrrell brothers in 1893, from Winnipeg to Edmonton, Fort Cipewyan, Chesterfield Inlet (Northwest Territories), Hudson's Bay and Churchill, Manitoba. Mode of access: Internet.